TINJAUAN ‘URF TERHADAP TRADISI PERKAWINAN SELASA WAGE (STUDI KASUS DI KELURAHAN KAJEN KECAMATAN KAJEN KABUPATEN PEKALONGAN) - Abiyyu Farid Hakim; Muhamad Ali Mustofa Kamal; Ika Setyorini (Kampus Akademik Publiser, 2026)
This study aims to determine the views of the people of Kajen Village regarding the marriage tradition conducted on Selasa Wage and to analyze the tradition from the perspective of 'urf. This research employs field research with a qualitative approach. The data were collected through interviews, observations, and documentation, and then analyzed using descriptive qualitative analysis. The results of the study indicate that the tradition of marriage on Selasa Wage is still practiced and maintained by the people of Kajen Village as a cultural heritage passed down from generation to generation. This tradition is understood as a cultural effort to attain inner peace, family harmony, and blessings in married life. Nevertheless, the community does not consider Selasa Wage as a determinant of the validity of a marriage, since the validity of marriage remains based on the fulfillment of the pillars and requirements of marriage according to Islamic law. From the perspective of 'urf, the tradition of marriage on Selasa Wage falls into the category of 'urf amali because it is manifested in the practices of the community in determining the time of marriage, and it is also classified as 'urf khass because it applies only to certain groups of people who still maintain the weton calculation tradition. Furthermore, this tradition is categorized as 'urf shahih because it does not contradict the Qur'an, Hadith, or the principles of Islamic law, does not alter the pillars and requirements of marriage, and contains benefits for the community. Therefore, the tradition of marriage on Selasa Wage can be accepted from the perspective of Islamic law as a customary practice that remains in accordance with Islamic principles.